A view most glorious [large type] - Scott, Regina, 1959- (Scott, Regina, 1959- American wonders collection, 2022)
"Reluctant socialite Coraline Baxter longs to live a life of significance and leave her mark on the world. When her local suffragette group asks her to climb Mount Rainier to raise awareness of their cause, she jumps at the chance, even though she has absolutely no climbing experience. If she can do it, any woman can do it. And after her mother issues an ultimatum--that Cora marry the man of her mother's choosing if she is not successful--Cora must do it. But she can't do it alone. Noted mountain guide Nathan Hardee initially refuses to help Cora, but has a change of heart when he sees what is at stake. He knows enough about the man Cora's mother has chosen to know that the headstrong young woman should have nothing to do with him, much less marry him. Climbing Rainier will require all of Cora's fortitude and will lead her and Nathan to rediscover their faith in God and humanity. These two loners make unlikely partners in righting a wrong and may just discover that only together is the view most glorious"--